Kersen Leaf Tea’s Effects on Male Mice’s Liver and Kidney Functions Induced by Alloxan - Wiyadi Wiyadi; Mustaming Mustaming; Rus Andraini (International Journal Labs, 2022)
Kersen leaf is a tree native to Southern America and Southern Mexico. In Indonesia, this tree is very easy to get because it grows a lot on the side of the streets. Empirically, Kersen leaves have been widely used by the public as one of the herbs or herbs to overcome various diseases, including DM disease. The study used True Experimental design with Pre and post Control Design design. The purpose of this study was to test the effect of using Kersen Leaf Tea on Hepar and Kidney function. Hepar function will be measured by assessing levels of Alanain Transminerase (ALT) Aspartate aminotransferases (AST). For kidney function is assessed by measuring Creatinine and Ureum levels. The results of the Shapiro test normality test obtained data that were not normally distributed so that the Bivariate test used alternative tests, namely the Kruscal Walis test and the Wilcoxon Test. The results of the study on the administration of kersen leaf tea there were differences between the Control group with the dose group of 2%, dose 4% and dose 6% at ALT levels (p = 0.000), AST levels (p = 0.005), and creatinine levels (p = 0.007) but there was no difference in Urium (P = 0.447). The results of the Wilcoxon test showed the effect of giving kersen leaf tea on ALT levels ( p = 0.018), AST levels (p = 0.000), Urium levels (p = 0.37) and creatinine levels (p = 0.038). The administration of kersen leaf tea improves liver and kidney function in Alloxan-induced male mice.